Comparison Of Orthopantomogram and Lateral Cephalogram for Gonial Angle, Mandibular Ramus Height And Body Length - Zulfiqar, Mobina Fatima; Zulfiqar, Kanwal; Bashir, Ulfat; Luqman, Uzair; Rizwan, Zarnab (Journal of Rawalpindi Medical College, 2024)
Objective: This study aims to compare orthopantogram and lateral cephalogram for gonial angle and mandibular linear measurements (ramus height and body length). Methods: A cross-sectional study was conducted at Islamic International Dental Hospital. A total of 195 patients, both genders, ages 16 to 35 years who were citizens of Pakistan and had clear radiographs, lateral cephalograms, and OPG available, were included. Patients with craniofacial malformations and facial asymmetry were excluded. The following variables were measured. (a) body length (Go-Me) (b) ramus height (Co-Go) and (c) gonial angle on both sides. An independent sample t-test was applied to compare mandibular measurements between two radiographs (OPG and lateral cephalograms). Results: The mean age of the participants was 24.24±5.39 years. The females were 111 (56.92%) and males were 84(43.08%). Measurements on the cephalogram and OPG on the right and left sides were almost similar. The mean value of ramus height on OPG (60.93±5.39mm) was higher than on cephalogram (58.69±6.15mm) statistically significant on the right side (p<0.001). Similar statistically significant results(p<0.001) were found for ramus height being increased in the OPG on the left side(60.92±5.39mm), and body length on both sides(109.41±6.08mm). However, the gonial angle on both radiographs and both sides was insignificant (p=0.058 for the right; p=0.062 for the left). Conclusion: For angular measures of the mandible, panoramic radiographs are equally accurate as lateral cephalograms, but physicians should use caution when assuming vertical and horizontal measurements from OPGs.